Bentuk, Jenis, dan Fungsi Tindak Tutur Ilokusi Penjual Dalam Menawarkan Dagangan di Pasar Kota Bukittinggi - Aisah Amini, Khofifah; Rahmi, Husni Mardhyatur (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
This research aims to describe the seller illocutionary speech act's form, type, and function in offering merchandise at the Bukittinggi City Market. This study is descriptive research that takes a qualitative approach. This research's data is in the form of the seller's speech when offering merchandise at the Bukittinggi City Market, specifically Lereng Market, Ateh Market, Bawah Market, Los Lambuang, and Ramayana. In the data provision stage, the matching method is used, tapping is the basic approach, and the listening-engagement technique (SLC) and free-engaged involved listening (SBLC) techniques are the follow-up techniques. In addition, recording and note-taking methods are utilized. In the data analysis stage, the matching approach is utilized, with the initial technique consisting of sorting the determining elements (PUP) and the subsequent technique consisting of differentiating comparisons (HBB). The results of the data analysis are provided informally. The result of this research, the types of speech acts employed by sellers to advertise their products include speech actions with a mode (1) declarative, (2) imperative, (3) interrogative, (4) imperative-interrogative, (5) interrogative-imperative, (6) imperative-declarative, and (7) imperative-declarative. The speech acts that are performed are direct and indirect. The role of illocutionary speech acts utilized by sellers to offer goods is in the form of illocutionary speech acts: (1) Forceful with the intent of implying and asserting; (2) Directive having the intent to command and coerce; (3) Commission intended for offering; and (4) Expressed to praise and appreciate